2014
DOI: 10.3402/qhw.v9.23376
|View full text |Cite|
|
Sign up to set email alerts
|

Difficulties in everyday life: Young persons with attention-deficit/hyperactivity disorder and autism spectrum disorders perspectives. A chat-log analysis

Abstract: This study focuses on the everyday life of young persons with attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). There are follow-up studies describing ADHD, and ASD in adults, and residual impairments that affect life. Few qualitative studies have been conducted on the subject of their experiences of everyday life, and even fewer are from young persons’ perspectives. This study's aim was to describe how young persons with ADHD and ASD function and how they manage their everyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Social decision making is often difficult, anxiety provoking and exhausting for autistic individuals (Ahlstrom & Wentz, 2014;Hull et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Social decision making is often difficult, anxiety provoking and exhausting for autistic individuals (Ahlstrom & Wentz, 2014;Hull et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that although well-meaning, parents of young adults with ASD may inadvertently restrict the lives of their children and also be perceived as being too controlling [28]. Further, some supports offered by universities can act more as barriers than facilitators to university engagement for students with ASD [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although devices have been developed to improve health in children [19], no specific devices have yet been made in Smart-Homes that help children, with or without ADHD, in carrying out their daily activities through IoT approaches, just like [17] raised in its review.…”
Section: B Smart-homementioning
confidence: 99%